Rina; THE CORRELATION BETWEEN TEACHER TEACHING SKILL PERCEPTION WITH THE STUDENTS’ MOTIVATION OF LEARNING JAPANESE AT MAN 2 SEMARANG - Rina Alaviah; Andy Moorad Oesman; Chevy Kusumah Wardhana (Chi'e: Journal of Japanese Learning and Teaching, 2017)
Abstrak Keterampilan mengajar guru merupakan kecakapan atau kemampuan seorang guru dalam melaksanakan dan mengelola kelas dalam proses kegiatan belajar mengajar. Oleh karena itu, keterampilan mengajar harus ada pada diri seorang guru. Apabila guru tidak memiliki keterampilan mengajar maka pembelajaran akan kurang efektif dan tujuan belajar tidak dapat tercapai dengan maksimal. Keterampilan mengajar guru merupakan salah satu faktor yang mempengaruhi motivasi belajar siswa. Tujuan dari penelitian ini untuk mengetahui korelasi antara persepsi keterampilan mengajar guru dengan motivasi belajar bahasa Jepang siswa di MAN 2 Semarang. Jenis penelitian ini adalah deskriptif kuantitatif. Populasi penelitian adalah seluruh siswa kelas XII IPA dan XII IPS MAN 2 Semarang. Sampel penelitian adalah siswa kelas XII IPA 4 dan XII IPS 1. Instrumen yang digunakan adalah lembar angket. Data dianalisis dengan rumus product moment. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang kuat antara variabel X (persepsi keterampilan mengajar guru) dan variabel Y (faktor - faktor motivasi belajar siswa). Hal ini ditunjukkan melalui uji korelasi. Dalam uji korelasi, nilai r hitung adalah 0,6129 jika ditafsirkan dengan tabel penafsiran angka korelasi termasuk ke dalam kategori kuat. Sedangkan r tabel adalah 0,232 (5%) dan 0,302 (1%). Karena nilai r tabel lebih kecil daripada r hitung, maka disimpulkan terdapat korelasi positif yang kuat. Dengan demikian hipotesis satu (H1) dalam penelitian ini diterima dan secara otomatis hipotesis nol (H0) ditolak. Abstract The teachers’ teaching skill is an efficiency or ability of a teacher when doing and arranging the class in the process of teaching and learning activity. So, the ability of teaching has to be in a teacher. While the teacher does not have the ability of teaching, the activity of learning will not be effective and the aim of learning can not be achieved maximally. The teachers’ teaching ability is one of the factor that influence the students’ learning motivation. The aim of this research is to know the correlation between the perception of teachers’ teaching ability with the students’ motivation in learning Japanese at MAN 2 Semarang. This kind of research is descriptive quantitative. The population of the research are all of the students of XII grade in Science and Social Class at MAN 2 Semarang. The sample of the research are students of XII Science 4 and XII Social 1 grade. The instrument used is questionnaire. The data analysis using product moment formula. From the result of the research showing that there is the strong positive relation between X variable (the perception of teachers’ teaching ability) with Y variable (the factors of students’ learning motivation). It is shown through the correlation test. In correlation test, the value of r is counted 0.6129 if it is interpreted to the table of correlation number interpretation include in the strong category. While r table is 0,232 (5%) and 0.302 (1%). Because of the value of r is smaller than r count, so it can be concluded thet there is strong positive correlation. So that the first hypothesis (H1) in the research is accepted and the zero hypothesis is rejected automatically.